ISIL’S EXTERNAL STRATEGY - Целуйко, М. Є. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The main directions and methods of ISIL’s external activity being  implemented since chaliphate proclamation are examined  in  the article. General strategy and priority of activities at the external territories  are  defined  based  on  each  of  eight  publicly  proclaimed  wilayats  (provinces)  internal situation. Expands ISILʼs policy on foreign territories and similarities and specific characteristics of each wilayat.